Analisis Struktur Biaya dan Keuntungan Usahatani Padi pada Kawasan Sentra Produksi Padi - Fastabiqul Khairad; Melinda Noer; Mahdi Mahdi (Universitas Medan Area, 2023)
This article aims to compare the cost and profit structures of rice farming in areas inside and outside the rice production centers in Agam Regency. The production center area is determined by the West Sumatra Provincial government through Governor Decree number 521.305.2013. This comparison was made to see the problem of whether the production center area can have an impact on the efficiency of farming activities compared to outside the center area. In order to examine this problem, the theoretical reference of cost analysis and calculation of farming profits is used. Data collected through secondary data and primary data from interviews with 120 rice farmers and analyzed descriptively quantitatively using a comparative T-test. The results of the study concluded that there were no significant differences in profits between areas inside and outside the production center areas. This can be interpreted that the policy of determining the center area has not been fully able to increase the cost efficiency of farming activities in the center area. For this reason, special efforts from the government are needed to develop production center areas as centers of production activities.